FRI0364 Real-World Incidence of Biologic Dose Escalation and Impact on Biologic Costs Among Patients with Rheumatoid Arthritis Treated with Intravenous Agents Abatacept, Infliximab or Tocilizumab. (9th June 2015) - Fowler, R.; McMorrow, D.; Smith, D.; Nadkarni, A.
Abstract : Background: Biologic dose escalation may be used to confer greater therapeutic benefit for patients (pts) with RA; however, escalated doses may increase the cost of treatment. Objectives: To quantify the real-world incidence of biologic dose escalation and its impact on biologic costs among pts with RA treated with the IV agents abatacept, infliximab or tocilizumab. Methods: This was a retrospective, observational cohort study using a large US administrative claims database. Pts included in the study had initiated IV abatacept, infliximab or tocilizumab between 1 January 2009 and 1 October 2012 (index), were continuously enrolled for 12 months before and ≥3 months after index, were aged ≥18 years at index and had ≥1 baseline medical claim with an ICD-9-CM diagnosis code for RA (714.0x). First-line initiators used no biologic pre-index; second-line initiators used only one biologic pre-index. Incidence of dose escalation was ascertained during a variable length follow-up period extending from index until censoring at biologic discontinuation, switch to another biologic, disenrollment from health insurance or 31 December 2012. Dose escalation was defined as a sustained increase (≥2 consecutive administrations) of ≥30% in the frequency or paid amount (indicating higher dose) of biologic administrations. The hazards of dose escalation were compared across biologics using multivariable Cox regression. Incremental impact of dose escalation on biologic cost was quantified for each biologic by comparing per-pt per-month (PPPM) biologic costs between those who did versus those who did not experience dose escalation using multivariable generalized linear models. Results: Study results are shown in the Table. Follow-up ranged from 261 days for first-line tocilizumab to 407 days for second-line infliximab. In both first- and second-line analyses, pts initiating IV abatacept had substantially lower hazards of biologic dose escalation (all p<0.01). In both first- and second-line analyses, dose escalation was associated with statistically significant increases in biologic cost for each biologic (all p<0.05). Incremental PPPM cost impacts of dose escalation on biologic costs were largest for infliximab and smallest for abatacept. Conclusions: In this real-world study of pts with RA initiating first- or second-line IV abatacept, infliximab or tocilizumab, pts initiating IV abatacept were least likely to escalate doses and had the lowest incremental impact of dose escalation on biologic cost. Disclosure of Interest: R. Fowler Grant/research support from: Bristol-Myers Squibb, Employee of: Truven Health Analytics, D. McMorrow Grant/research support from: Bristol-Myers Squibb, Employee of: Truven Health Analytics, D. Smith Grant/research support from: Bristol-Myers Squibb, Employee of: Truven Health Analytics, A. Nadkarni Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb